A No-Brainer! The Therapeutic Potential of TRIM Proteins in Viral and Central Nervous System Diseases - Hage, Adam; Janes, Mikhaila; Best, Sonja M. (Viruses, 2025)
Tripartite motif (TRIM) proteins comprise an important class of E3 ubiquitin ligases that regulate numerous biological processes including protein expression, cellular signaling pathways, and innate immunity. This ubiquitous participation in fundamental aspects of biology has made TRIM proteins a focus of study in many fields and has illuminated the negative impact they exert when functioning improperly. Disruption of TRIM function has been linked to the success of various pathogens and separately to the occurrence and development of several neurodegenerative diseases, making TRIM proteins an appealing candidate to study for novel therapeutic approaches. Here, we review the current findings on TRIM proteins that demonstrate their analogous properties in the distinct fields of viral infection and central nervous system (CNS) disorders. We also examine recent advancements in drug development and targeted protein degradation as potential strategies for TRIM-mediated therapeutic treatments and discuss the implications these technologies have on future research directions.